2021
DOI: 10.1016/j.rmed.2020.106290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of patient immunodeficiencies on the diagnostic performance of serological assays to detect Aspergillus-specific antibodies in chronic pulmonary aspergillosis

Abstract: Background Prevalence of chronic pulmonary aspergillosis (CPA) is ~3 million patients worldwide, and detection of Aspergillus -specific antibody is a critical diagnostic component. Some patients with CPA have subtle immune deficits possibly contributing to poor Aspergillus antibody production and false negative results. Materials/methods We analyzed patient data from 167 cases of clinically confirmed CPA previously e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…We observed no significant statistical difference in the rate of CPA in HIV-positive patients and CPA in HIV-negative patients (6.8% vs 10.9%), contrary to other studies. 6 , 16 , 22 , 33 Though Aspergillus serology was positive in less than 10% of our screened patients, it contributed to greater than 90% of CPA diagnosis. One CPA patient who was HIV-positive had a negative Aspergillus IgG and IgM LFA result.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We observed no significant statistical difference in the rate of CPA in HIV-positive patients and CPA in HIV-negative patients (6.8% vs 10.9%), contrary to other studies. 6 , 16 , 22 , 33 Though Aspergillus serology was positive in less than 10% of our screened patients, it contributed to greater than 90% of CPA diagnosis. One CPA patient who was HIV-positive had a negative Aspergillus IgG and IgM LFA result.…”
Section: Discussionmentioning
confidence: 76%
“…This maybe because of a reduced capacity to elicit production of antibodies; the correlation between immunodeficiency and negative Aspergillus serology has been previously described. 6 , 9 , 33 Unfortunately, the participant in the control group with a positive Aspergillus antibody test was unable to be reached for imaging and further laboratory investigations to evaluate the clinical relevance. It could have been a possible case of asymptomatic pulmonary aspergillosis or a false positive test.…”
Section: Discussionmentioning
confidence: 99%
“…Disregarding Aspergillus species, it was suggested that host immunodeficiency may influence the positivity of Aspergillus antibody tests ( 11 ). In this study, to the best of our knowledge, there were no immunodeficiency factors associated with false-negative results in the Aspergillus precipitin tests.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the sensitivity of the precipitin test has ranged from 59% to 88% in patients with CPA ( 8 , 10 ). It was suggested that the false-negative results in Aspergillus antibody tests were caused by the host immune deficiency ( 11 ) and Aspergillus species ( 12 ). The causative organism associated most commonly with CPA is Aspergillus fumigatus , and the efficacy of Aspergillus antibody testing has been proven in most cases of A. fumigatus -associated CPA ( 8 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The performances of some Aspergillus -specific antibody assays are negatively affected by the relatively common minor or subtle immunodeficiencies found in CPA patients. However, the LDBio Aspergillus -specific IgG and IgM assay has been previously reported to be minimally affected by immunodeficiency, and thus, it may perform acceptably well in both HIV seronegative and seropositive patients [ 29 ]. Notwithstanding, CPA is rarely associated with HIV, and it is more common in patients without apparent or with subtle immunodeficiency.…”
Section: Discussionmentioning
confidence: 99%